EFEKTIVITAS PENGGUNAAN METODE IQRA` DALAM PENINGKATKAN KUALITAS BACAAN AL QURAN SANTRI DI PONDOK PESANTREN TAHFIDZ AL-BAROKAH MERAPI TAHUN AJARAN 2022/2023 - Susanto, Lukman Taufik Hidayat; Subando, Joko; Widoyo, Agus Fatuh (Institut Islam Mamba'ul 'Ulum Surakarta, 2024)
The Iqra` method is a method in the process of learning to read the Qur'an which in the learning process begins at the basic level and emphasizes direct reading practice because in the learning process it has an efficient and practical learning systematic. According to the situation in the field, this research is based on the fact that there are many students who do not understand the law of recitation and are not fluent in reading the Qur'an. This study has a goal, namely to determine the effectiveness of using the iqra` method in improving the quality of reading the Koran. The method used in this research is to use a quantitative approach, then the sample used is 53 people and divided into 2 sample groups, namely the iqra` method group and the non iqra` method group. Then in collecting the data, the researcher uses the test technique, then the results of the research are carried out by testing the prerequisite test with the homogeneity test and the normality test, then the next step is to test the hypothesis with the T Test Technique to find out the value of the difference in the results of using the iqra` method and non iqra` method in increasing the quality of reading the Qur'an. Based on the results of the research and discussion, the results are T count 3.448 > 1.711 T table and the significance results are 0.002 <0.05 so that the hypothesis in this study is accepted. The use of the iqra` method in improving the quality of students' Al-Qur`an reading at the Tahfidz Al-Barokah Islamic Boarding School in Merapi is considered effective.